Peranan Fosfor dalam Meningkatkan Toleransi Tanaman Sorgum terhadap Cekaman Aluminium - Lestari, Tri; ,, Trikoesoemaningtyas; Ardie, Sintho Wahyuning; Sopandie, dan Didy (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
The management of P nutrition can be a good solution for aluminum toxicity and P nutrient deficiency in acid soil. This study aimed to determine the role of phosphorus in improving the tolerance of sorghum to Al stress in nutrient culture. This research was conducted at green house of IPB Bogor, tissue culture laboratory in the Department of AGH IPB and Balai Besar Pasca Panen Cimanggu Bogor, from January to November 2014. A completely randomized factorial design was used in three experiments. The results revealed that addition of P improved the tolerance of two sorghum genotypes to Al stress as indicated by the reduction in root length inhibition by Al, where  P was more effective in tolerant genotype Numbu. Addition of P reduced the accumulation of Al in the root tissues as shown by the lighter intensity of hematoxylin staining, especially in Numbu. Aluminum stress increased the secretion of oxalate acid in both sorghum genotypes, where P lowered oxalate acid secretion in both genotypes. These facts showed that the role of P in improving the tolerance of sorghum to Al stress might be associated with the inhibition of Al absorption into the root tissues, although the mechanism is not yet known.Keywords: Al stress, organic acid secretion, role of P, root staining method, sorghum